Plural creativity: Overview, challenges, and perspective for academic production in Management - Freitas, Rafaela Gonçalves; Davel, Eduardo (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
Plural creativity is a growing interest in the management field of research. Academic production, however, remain dispersed, without consolidation and understanding of this perspective. This article aims to review, integrate, and consolidate academic production on plural creativity in management. The research is based on a systematic review of national and international academic production in the field of management. The analysis of academic production generated four categories: group creativity, team creativity, collective creativity, and collaborative creativity. The analysis of the categories revealed two central approaches: creativity as a result and creativity as a process. Our results contribute to the consolidation of an integrated understanding of plural creativity.